Pendekatan Multidisipliner Sains Sosial dalam Pembelajaran Pendidikan Agama Islam (PAI) - Saifuddin; Atmaja, Kusuma; Mulyani, Surtimah; Ainun, Amma; Ilham; Mulyadin, Wahyu; Abdillah Putra, Andy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the implementation of a multidisciplinary social science approach in Islamic Religious Education (PAI) learning. The problem underlying this research is the dominance of normative and textual teaching methods that cause students to have limited contextual understanding of Islamic values in social life. The purpose of the study is to analyze how the integration of social sciences such as sociology, anthropology, psychology, and history in PAI learning can enhance students’ critical thinking, social awareness, and holistic understanding of Islamic teachings. This research employed a qualitative descriptive method, with data collected through classroom observations, in-depth interviews with teachers and students, and documentation analysis. The results show that the application of a multidisciplinary approach makes the learning process more interactive, contextual, and meaningful. Students demonstrate a better ability to relate Islamic values to contemporary social issues, such as tolerance, environmental awareness, and social justice. In addition, this approach contributes positively to the development of students’ character, including empathy, responsibility, and respect for diversity. Thus, the multidisciplinary social science approach is proven to be effective in strengthening the relevance of PAI learning in responding to the challenges of modern society.